Pertussis in Lao PDR: Seroprevalence and disease - Daria Kleine; Somxay Billamay; Phetsavanh Chanthavilay; Sodaly Mongkhoune; Chirapha Keokhamphoui; Chanthala Souksakhone; Phonethipsavanh Nouanthong; Bouaphan Khamphaphongphane; Claude P. Muller; Antony P. Black (International Journal of Infectious Diseases, 2020)
Objectives: Pertussis is a debilitating vaccine-preventable infection. The aim of this study was to determine susceptibility and exposure to pertussis in Lao PDR in different age groups and subpopulations. Methods: A total 3072 serum samples were obtained from different cohorts: children with documented vaccination, pre-schoolers, schoolchildren, blood donors, healthcare workers (HCWs), and pregnant women and paired cord blood. Samples were tested for anti-pertussis toxin IgG antibodies. A history of Bordetella pertussis exposure was defined according to antibody titres. Four hundred and seventy-five throat swabs and nasopharyngeal aspirates were analysed by PCR for the presence of B. pertussis in symptomatic children at the Children's Hospital in Vientiane. Results: Overall pertussis seroprevalence was 57.5%. The prevalence of titres indicating acute infection or recent vaccination or infection/vaccination within the last 12 months ranged from 7.4% (100/1356) in adults to 21.4% (25/117) in pre-schoolers (age 1–5 years). B. pertussis was detected in 1.05% (5/475) of children with respiratory symptoms in Vientiane Capital. Conclusions: It is suggested that routine childhood vaccination, in particular outreach, as well as vaccination of HCWs should be strengthened. A childhood booster and vaccination of pregnant mothers should be considered. There is also a need to improve reporting and to introduce pertussis testing in at least one central facility.